2006
DOI: 10.1038/ng1872
|View full text |Cite|
|
Sign up to set email alerts
|

Lamin B1 duplications cause autosomal dominant leukodystrophy

Abstract: Adult-onset autosomal dominant leukodystrophy (ADLD) is a slowly progressive neurological disorder characterized by symmetrical widespread myelin loss in the central nervous system, with a phenotype similar to chronic progressive multiple sclerosis. In this study, we identify a genomic duplication that causes ADLD. Affected individuals carry an extra copy of the gene for the nuclear laminar protein lamin B1, resulting in increased gene dosage in brain tissue from individuals with ADLD. Increased expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
336
0
7

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 362 publications
(354 citation statements)
references
References 48 publications
11
336
0
7
Order By: Relevance
“…The genetic basis of the disease became known after initiating this study,6, 17 and two asymptomatic subjects without MRI pathology were found to be noncarriers of the LMNB1 duplication. These two individuals were excluded from the study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The genetic basis of the disease became known after initiating this study,6, 17 and two asymptomatic subjects without MRI pathology were found to be noncarriers of the LMNB1 duplication. These two individuals were excluded from the study.…”
Section: Methodsmentioning
confidence: 99%
“…This type of ADLD is caused by a duplication of the lamin B1 gene ( LMNB1 ) and increased expression of lamin B1,6, 7 which, in turn, seems to affect maturation of oligodendrocytes 8. Cases have been reported from Brazil, Canada, France, Germany, Ireland, Israel, Italy, Japan, Serbia, Sweden, and the United States, among other countries 6, 7, 9, 10, 11, 12, 13, 14, 15, 16.…”
mentioning
confidence: 99%
“…However, autosomal-dominant leukodystrophy, a neurodegenerative disease caused by myelin loss in the central nervous system, was recently found to be associated with a duplication of the lamin B1 gene. It is not clear how duplication of how the lamin B1 gene results in such a tissue-specific disease, although it was suggested that such an alteration may lead to the generation of autoantibodies resulting in demyelination [63].…”
Section: Laminopathies Associated With Mutations In the B-type Laminsmentioning
confidence: 99%
“…Mutations in B‐type lamins have also been described, enlarging the field of laminopathies. Thus, heterozygous mutations in LMNB2 have been reported to predispose to the development of acquired partial lipodystrophy (APLD), also called “Barraquer‐Simons syndrome” (Hegele et al., 2006), and duplication of LMNB1 leads to adult‐onset autosomal‐dominant leukodystrophy (ADLD; Padiath et al., 2006). …”
Section: Lamins and Laminopathiesmentioning
confidence: 99%
“…The autosomal‐dominant leukodystrophy (ADLD, OMIM # 169500) is the only laminopathy currently linked to the gene LMNB1, mainly caused by its duplication (Padiath et al., 2006). Clinically, this disease is a progressive degenerative neurological disorder with cerebellar, autonomic, and pyramidal abnormalities.…”
Section: Mirnas In Hereditary Laminopathiesmentioning
confidence: 99%